The lost crown of Sodor - Stubbs, Tommy; Allcroft, Britt; Awdry, W. (New York : Random House, 2013)
Thomas helps the Earl restore Ulfstead Castle and makes friends with an old engine named Stephen.
"Based on The Railway Series by The Reverend W Awdry."
"Created by Britt Allcroft."
"As seen on DVD! King of the railway, the movie."
Keywords: Thomas, -- the Tank Engine (Fictitious character) -- Juvenile fiction; Steam-engines -- Juvenile fiction; Lost articles -- Juvenile fiction